New species of and taxonomic notes on Anastrepha (Diptera: Tephritidae) - Norrbom, Allen L.; Korytkowski, Cheslavo A. (Zootaxa, 2011)
Seven new species of Anastrepha are described and illustrated: A. conflua (Costa Rica), A. levefasciata (Perú), A. nolazcoae (Perú), A. paradentata (Mexico), A. raveni (Perú), A. trivittata (Brazil: Amazonas), and A. woodleyi (Bolivia). Anastrepha nunezae Steyskal, 1977, is recognized as a synonym of A. mucronota Stone, 1942, and A. pseudanomala Norrbom is recorded for the first time from Ecuador.